2020
DOI: 10.3390/cells9071637
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modulation of Mitochondria–Endoplasmic Reticulum Contact Sites

Abstract: Contact sites between mitochondria and endoplasmic reticulum (ER) are points in which the two organelles are in close proximity. Due to their structural and functional complexity, their exploitation as pharmacological targets has never been considered so far. Notwithstanding, the number of compounds described to target proteins residing at these interfaces either directly or indirectly is rising. Here we provide original insight into mitochondria–ER contact sites (MERCs), with a comprehensive overview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 136 publications
(174 reference statements)
1
18
0
Order By: Relevance
“…Other studies have used a similar approach to look at variations between proteins in MERCS during viral infection [ 34 ], in diabetes [ 35 ] and in mice with caveolin-1 (a pivotal regulator of cholesterol and component of MERCS) knocked out [ 36 ]. Recently, Magalhães Rebelo and colleagues clustered the common proteins identified in these different studies and showed that approximately 650 proteins in mouse brain tissue were found in three of the other aforementioned independent studies [ 31 , 33 , 37 ], but only 18 of these proteins were commonly found in all the aforementioned studies involving the mouse brain, liver and testis [ 37 ], suggesting that the MERCS proteome might be tissue-specific. They also showed that approximately 1190 proteins were found in two different immortalised human liver cells [ 31 , 32 , 35 ].…”
Section: Mitochondria–er Contact Sites and Mitochondria-associatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have used a similar approach to look at variations between proteins in MERCS during viral infection [ 34 ], in diabetes [ 35 ] and in mice with caveolin-1 (a pivotal regulator of cholesterol and component of MERCS) knocked out [ 36 ]. Recently, Magalhães Rebelo and colleagues clustered the common proteins identified in these different studies and showed that approximately 650 proteins in mouse brain tissue were found in three of the other aforementioned independent studies [ 31 , 33 , 37 ], but only 18 of these proteins were commonly found in all the aforementioned studies involving the mouse brain, liver and testis [ 37 ], suggesting that the MERCS proteome might be tissue-specific. They also showed that approximately 1190 proteins were found in two different immortalised human liver cells [ 31 , 32 , 35 ].…”
Section: Mitochondria–er Contact Sites and Mitochondria-associatedmentioning
confidence: 99%
“…However, due to the complexity, organization and dynamics of MERCS, finding a drug that allows their modulation and, particularly, a single function/type of contacts might be extremely challenging. Thus, structural system pharmacology, which combines large-scale experimental studies with computational modelling, has been suggested as a possible method to develop efficient drugs to modulate MERCS [ 37 ]. In agreement with Magalhães Rebelo and colleagues, we believed that drugs can affect MERCS mainly via three different pathways: by direct interaction with proteins in MERCS, by affecting protein expression levels or by modulating upstream signalling pathways that result in the alteration of the ultrastructure and/or function of MERCS [ 37 ].…”
Section: Mercs As a Drug Targetmentioning
confidence: 99%
“…Therefore, MERCs proteins potentially could be used as molecular targets in creating a new neuroprotective approach. Taking that into account, the link between MERCs functions and the pathogenesis of such neurodegenerative pathologies as Alzheimer's, Parkinson's, and Huntington's diseases received much attention recently due to the novel observations (De Mario et al, 2017;Moltedo et al, 2019;Magalhães Rebelo et al, 2020).…”
Section: The Emerging Role Of Mercs In Supporting Neurotransmission Dmentioning
confidence: 99%
“…In eukaryotic cells, the ER is the site of protein synthesis, modification, and folding [ 15 ]. Mitochondria are the most important organelles for supplying energy and regulating cell survival [ 16 ]. The ER and mitochondria share an interconnected region in which the molecular components are involved in an interaction mechanism to create a stable environment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%